How did Japanese households change their food purchasing behavior at the initial period of the COVID-19 outbreak? - Shigeru Matsumoto; Tsunehiro Otsuki (Cogent Economics & Finance, 2024)
Fearing the COVID-19 infection, people began to avoid eating out and eating at home. Simultaneously, they began using meal delivery services. Numerous studies have assessed the impact of COVID-19 on various economic activities. However, its effects on food consumption patterns have not yet been fully examined. By analyzing household spending data from 1448 households in Tokyo, Tokai, and Kinki areas of Japan, we observed changes in food spending before and after the pandemic. During the emergency, the share of expenditures on food-away-from-home (FAFH) decreased by 1.8%, the share of expenditures on food-at-home (FAH) increased by 0.5%, and the share of expenditures on food delivery services (FDS) increased by 1.3% for all eligible households. However, the extent of the shift from FAFH to FAH and FDS varied widely across households. Single-person and single-parent households continued to rely on FAFH during the pandemic, whereas parent-child households shifted more to FAH. This suggests that time-constrained households could not prioritize meal preparation even during the pandemic. While various policies have recently been introduced to promote healthy eating at home, our empirical findings suggest that policies to ease household time constraints are simultaneously required for these programs to work. During the COVID-19 pandemic, people spent more time at home, ate out less frequently, and started cooking at home. However, the extent to which eating habits changed during the pandemic varied greatly among households. Households with parents and children substantially shifted towards eating at home, while single-person households and households with single parents continued to eat out during the pandemic. These results indicate that people with limited time found it very challenging to change their eating habits.
Keywords: D12; I14; Q13; 330; COVID-19; food delivery services; food-at-home; food-away-from-home; household spending data